71.1k views
0 votes
Given these what is X if B-X=A

Given these what is X if B-X=A-example-1
Given these what is X if B-X=A-example-1
Given these what is X if B-X=A-example-2

2 Answers

5 votes

Answer:

answer is B

Explanation:

User Michael Irigoyen
by
5.1k points
5 votes

Answer:

B

Explanation:

B-X=A

or

B-A=X

or

X=B-A


X=\left[\begin{array}{ccc}-5&-1&6\\4&1&2\\0&-3&2\end{array}\right] -\left[\begin{array}{ccc}-1&-2&3\\4&8&-6\\0&1&5\end{array}\right] \\=\left[\begin{array}{ccc}-5+1&-1+2&6-3\\4-4&1-8&2+6\\0-0&-3-1&2-5\end{array}\right] \\=\left[\begin{array}{ccc}-4&1&3\\0&-7&8\\0&-4&-3\end{array}\right]

User Sean Bannister
by
5.4k points